A Study of Vocational Education and Training System in India: Examining the State of Vocational Education in India (Journal of Advances and Scholarly Researches in Allied Education, 2022)
India is at the cusp of demographic transition and is currently going through a 'demographicdividend'. This has presented a challenge to policy makers to ensure that there are enough employmentopportunities for the ever-expanding labor force. Skill development is one of the areas which is in urgentneed of reform. Vocational education depends on business and occupation and it is very important forevery nation to have a solid professional training framework. This can be characterized as gifted basedinstruction. Vocational education helps in financial development and the study in which discussed aboutvocational education, Vocational education and economic development, Development of vocationaleducation in India, The technical and vocational education training system, All India council oftechnical education, Current structure of vocational technical education in India